Peningkatan Kemampuan Memahami Lambang Bilangan 1-10 Menggunakan Media Kartu Angka pada Anak Tunagrahita Ringan Kelas 1 SLB Asuhan Kasih Kupang - Lero, Alviana Sare; Selan, Ot Bil Wilson; Wangge, Vinsensius; Ajito, Timoteus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the ability to understand and sequence number symbols in students with mild intellectual disabilities in Grade I at SLB Asuhan Kasih Kupang. The main problem found is that learning is still abstract, making it difficult for students to recognise and sequence the symbols for numbers 1–10. This study uses a classroom action research design based on the Kemmis and McTaggart model, which was implemented in two cycles. There were three students participating in this study. Data were collected through observation, tests, and documentation. The results showed a significant improvement from the pre-cycle to each action cycle. In cycle I, the students' abilities were still in the very low category. After using number cards that were presented in a concrete and interesting manner and repeated several times, there was an improvement in the students' ability to understand the symbols for numbers 1–10 and sequence them correctly. At the end of cycle II, all students achieved the predetermined success criteria with scores of RN (95), PB (95), and NF (90). These findings indicate that number card media effectively help students with mild intellectual disabilities process information more concretely and increase their focus and engagement during learning. Thus, number card media can be a relevant learning alternative to improve basic mathematical skills for students with mild intellectual disabilities